The Corn Bounty Experiment of Charles II - Gras, N. S. B. (Quarterly Journal of Economics, 1910)
Journal Article The Corn Bounty Experiment of Charles II Get access N. S. B. Gras N. S. B. Gras Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 24, Issue 2, February 1910, Pages 419–422, https://doi.org/10.2307/1883563 Published: 01 February 1910